2019
DOI: 10.21002/jaki.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Ego Depletion and Its Effect on Auditors’ Judgment and Decision-Making Quality

Abstract: This study aimed to examine the determinants of ego depletion and its effect on judgment and decision-making (JDM) quality. Auditing is one of the professions vulnerable to ego depletion, which is a temporary state of lack of cognitive resources to self-control caused by physical or psychological fatigue. Data were collected via online survey on 121 auditors in Indonesia who were selected by convenience sampling. The results showed that interpersonal conflict positively affected ego depletion. In line with ego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(94 reference statements)
2
1
0
Order By: Relevance
“…From this, it can be concluded that the lower the quality of management decision making (JDM) of an auditor, the higher the level of ego depletion experienced, and vice versa. Previous studies by Hurley (2019), Mullis and Hatfield (2018) and Mursita et al (2019) have put forward similar predictions. H3: Ego depletion has a negative effect on audit judgment quality.…”
Section: The Effect Of Ego Depletion On Audit Judgmentsupporting
confidence: 68%
See 2 more Smart Citations
“…From this, it can be concluded that the lower the quality of management decision making (JDM) of an auditor, the higher the level of ego depletion experienced, and vice versa. Previous studies by Hurley (2019), Mullis and Hatfield (2018) and Mursita et al (2019) have put forward similar predictions. H3: Ego depletion has a negative effect on audit judgment quality.…”
Section: The Effect Of Ego Depletion On Audit Judgmentsupporting
confidence: 68%
“…The quality of auditors' judgment decision making (JDM) decreases as their level of ego depletion increases, and vice versa. Similar opinions have been conveyed by Hurley (2019), Mullis andHatfield (2018), andMursita et al (2019). These five respondents mostly agreed that ego depletion can affect their audit judgment.…”
Section: Hypothesis Testingsupporting
confidence: 68%
See 1 more Smart Citation
“…The findings of the study conducted by Libby & Lipe in 1992) demonstrate that task complexity serves as a motivational mechanism to enhance the calibre of an auditor's performance. Auditors face challenging work conditions that require increased effort, but they also acquire valuable information and experience while carrying out their assigned audit tasks (Mursita et al, 2019). The performance exhibited by the auditor is inherently intertwined with the auditor's individuality.…”
Section: Introductionmentioning
confidence: 99%